1987
DOI: 10.1111/j.1751-1097.1987.tb07894.x
|View full text |Cite
|
Sign up to set email alerts
|

THE α‐OXIDASE SYSTEM OF YOUNG PEA LEAVES (Pisum sativum) AS GENERATOR OF ELECTRONICALLY EXCITED STATES. EXCITATION IN THE DARK UNDER NATURAL CONDITIONS

Abstract: Abstract. The aerobic oxidation of saturated long chain fatty acids to the lower aldehyde and CO2 catalyzed by the α‐oxidase system of young leaves from germinating Pisum sativum results in concomitant excitation of the chloroplasts or/and fractions present in the α‐oxidase preparation. The excitation is attested to by both chlorophyll emission and Hill activity. This is the first case of photobiochemistry without light within a natural system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Addition of long chain fatty acids to preparation4 from peas (Pihum sativum)-which are known to contain broken chloroplasts-results in red emission and Hill activity (Salim-Hanna et al, 1987). The excitation of the chloroplasts appears not to be brought about by excited species derived from the cleavage of the a-peroxylactone, but rather by a CIEEI, process between the a-peroxylactone and exposed chlorophyll (Eq.…”
Section: Peroxidase Systemsmentioning
confidence: 99%
“…Addition of long chain fatty acids to preparation4 from peas (Pihum sativum)-which are known to contain broken chloroplasts-results in red emission and Hill activity (Salim-Hanna et al, 1987). The excitation of the chloroplasts appears not to be brought about by excited species derived from the cleavage of the a-peroxylactone, but rather by a CIEEI, process between the a-peroxylactone and exposed chlorophyll (Eq.…”
Section: Peroxidase Systemsmentioning
confidence: 99%
“…Using 1_14C labelled myristic acid, a correlation between release of radioactivity (as CO 2 ) and emission is observed (Salim-Hanna et al,1987). It may be significant that the excitation of the chloroplasts is observed only with preparations from very young leaves.…”
Section: -Thiouridinementioning
confidence: 93%
“…Important results obtained with this system are summarized in Scheme 2 (Cilento, 1984;Nassi and Cilento, 1985;Duran et al, 1986). When prepared from peas (Pisum sativum) this system contains broken chloroplasts; addition of the fatty acid results in red emission and Hill activity (Salim-Hanna et al, 1987). The excitation of the chloroplasts appears to be brought about by a CIEEL (Schmidt and Schuster, 1980) process between the a-peroxylactone and exposed chlorophylls.…”
Section: Hcoohmentioning
confidence: 99%
“…1 represent the differences between the presence and absence of the substrate in the cucumber powderkhlorophyll system. As in the case of the Pisum sativum preparation (Salim-Hanna et al, 1987), oxygen uptake is slow and tends to level off. Throughout the period of the present study, different preparations showed significant variations in the rate of oxygen uptake as reported by Baardseth et al (1987) both in the absence and presence of the fatty acid.…”
Section: Cucumber Preparationmentioning
confidence: 96%